Determination of haematological and biochemical abnormalities in HIV/AIDS infected patients receiving highly active antiretroviral therapy at the Effiankwanta Regional Hospital in the Western Region. - Afari, Samuel Kwadwo (2017)
A thesis submitted to the Department of Clinical Microbiology, College of Health Sciences, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of degree of Master of Science in Clinical Microbiology, 2016.